Coordinated conformational changes in P450 decarboxylases enable hydrocarbons production from renewable feedstocks - Wesley Cardoso Generoso; Alana Helen Santana Alvarenga; Isabelle Taira Simões; Renan Yuji Miyamoto; Ricardo Rodrigues de Melo; Ederson Paulo Xavier Guilherme; Fernanda Mandelli; Clelton Aparecido Santos; Rafaela Prata; Camila Ramos dos Santos; Felippe Mariano Colombari; Mariana Abrahão Bueno Morais; et al. (Nature Communications)
Abstract Fatty acid peroxygenases have emerged as promising biocatalysts for hydrocarbon biosynthesis due to their ability to perform C-C scission, producing olefins - key building blocks for sustainable materials and fuels. These enzymes operate through non-canonical and complex mechanisms that yield a bifurcated chemoselectivity between hydroxylation and decarboxylation. In this study, we elucidate structural features in P450 decarboxylases that enable the catalysis of unsaturated substrates, expanding the mechanistic pathways for decarboxylation reaction. Combining X-ray crystallography, molecular dynamics simulations, and machine learning, we have identified intricate molecular rearrangements within the active site that enable the Cβ atom of the substrate to approach the heme iron, thereby promoting oleate decarboxylation. Furthermore, we demonstrate that the absence of the aromatic residue in the Phe-His-Arg triad preserves chemoselectivity for alkenes, providing a distinct perspective on the molecular determinants of decarboxylation activity. Ultimately, these findings enable the sustainable production of biohydrocarbons from industrial feedstocks.